Peningkatan Hasil Belajar Pengembangan Kognitif Anak Usia Dini Melalui Model Example Non Example di TK Idhata Malalayang Kota Manado - Mieke F. Tiwow (Peneliti.net, 2022)
The goal to be achieved in this study is to get an overview of the application of examples non examples models in improving learning outcomes of cognitive development in early childhood at Idhata Malalayang Kindergarten, Manado City. This research is a class action research and the model used is a process model (Kemmis & Taggart, 1988). The learning model with 2 learning models was developed through 2 research cycles. In each research cycle is taken through four stages of research concerning: planning, implementation of activities, observation and reflection. The main data in this study are PG-PAUD teachers and students who are the research subjects. The results achieved in this study were in the first cycle the formative average value was 30% (15 students) and in the second cycle the formative average value was 90% (15 students). This shows that the results achieved are strongly influenced by the increased results and students' abilities in learning determined by several aspects in the Example Non Example learning model such as: (1) learning that is tailored to the interests and needs of children, (2) providing direct experience to children, (3) child-centered learning, and (4) evaluation is carried out both by the students themselves as well as with the teacher to see learning gains based on the success criteria for achieving the goals set in the learning design. So it can be concluded that the application of the Example Non Example learning model can improve the learning outcomes of PAUD students in cognitive development.